The Success Factors of Small Business in Crisis Condition: A Systematic Review - Zulfa, Inayati Fadhilah; Zuraida, Umi; Muthahhari, Muwahid (Integrasi Sains Media, 2024)
This systematic review examines the success factors of small businesses, particularly Micro, Small, and Medium Enterprises (MSMEs), during economic crises. Utilizing a systematic literature review (SLR) approach, the study identifies key elements that contribute to business resilience and performance in adverse conditions. The research highlights that physical and mental health, excellent customer service, support from family and friends, effective cash and liquidity management, adaptability, technology adoption, government support, and innovative business models are crucial for MSMEs' success during crises. The review further discusses how these factors enable businesses to navigate uncertainties, maintain operations, and thrive. This study aims to provide actionable insights for entrepreneurs, policymakers, and researchers to support small businesses in crisis conditions, fostering economic recovery and stability.